Kinerja Karyawan CV Salma Mandiri dipengaruhi oleh Pelatihan melalui Kompetensi - Ezra Christian; Edy Sanusi Silitonga (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to analyze the effect of training on employee performance at CV. Salma Mandiri, with a focus on the role of competence as an intervening variable. A quantitative approach was employed using path analysis to explain the relationships among training, competence, and employee performance. Primary data was collected through questionnaires distributed to employees of the company. The results show that: 1) Training has a positive and significant effect on employee performance; 2) Competence also has a positive effect on performance, but it is not statistically significant; 3) Training has a positive and significant effect on competence; 4) The of direct and indirect effects shows that the direct effect of training on performance is greater than the indirect effect through competence, indicating that competence does not mediate the relationship between training and employee performance at CV. Salma Mandiri